2013
DOI: 10.3340/jkns.2013.53.5.297
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Stalk Hemangioblastoma in a von Hippel-Lindau Patient : Clinical Course Follow-Up Over a 20-Year Period

Abstract: Supratentorial hemangioblastomas (HBs) are rare, and pituitary stalk HBs are extremely uncommon; therefore, pituitary stalk evaluation is often overlooked. Herein, we report the development of pituitary stalk HB over a 20-year period and the importance of regular long-term follow up for patients with HBs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Therefore, supratentorial HBLs including pituitary stalk HBLs are rare, accounting for only 2.1-2.9% of all HBLs 1 8 11 14) . Furthermore, HBLs occurring in the pituitary stalk are extremely rare with only 14 reported cases 2 5 6 7 9 10 11) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, supratentorial HBLs including pituitary stalk HBLs are rare, accounting for only 2.1-2.9% of all HBLs 1 8 11 14) . Furthermore, HBLs occurring in the pituitary stalk are extremely rare with only 14 reported cases 2 5 6 7 9 10 11) .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the excessive vascularity of the lesion and its proximity to critical neural structures including the pituitary stalk, optic apparatus, and hypothalamus sometimes precludes complete excision 14) . However, we thought that complete surgical excision was the optimal treatment strategy for sporadic pituitary stalk HBLs when its rising growth pattern or symptomatic presentation is taken into account 9) . This is because subtotal excision is associated with a high incidence of local disease progression requiring consideration of adjuvant radiosurgery 3 6) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it was concluded that other VHL disease intensifies the VHL HB during pregnancy, therefore surveillance is necessary. A case of a 15-year-old boy with intermittent vomiting and headache has been discussed in the report [26]. The case was identified to be supratentorial HB case which is rare.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To date, only 16 cases have been described. 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 We report the 17th case of pituitary stalk HBL with a literature review focusing on appropriate treatment modalities and prognosis.…”
Section: Introductionmentioning
confidence: 99%